In Vivo Bioassay of the Repellent Activity of Caraway Essential Oil against Green Peach Aphid - Jessica Girardi; Kristīne Berķe-Ļubinska; Ieva Mežaka; Ilva Nakurte; Gundars Skudriņš; Laura Pastare (Insects, 2023)
An in vivo dual choice bioassay with white cabbage as a host plant was used to determine the repellent effect of three different accessions of caraway (Carum carvi L.) essential oils (EOs) against the green peach aphid Myzus persicae (Sulzer). The dominant components of the EO were D-Carvone (47.3–74.4%) and D-limonene (25.2–51.9%), which accounted for 99.2–99.5% of the EOs determined by GC/MS. The EO with the highest D-limonene content (51.9%) showed the highest repellence (Repellency Index (RI) = +41%), which was stable up to 330 min. The incorporation of several surfactants with different hydrophilic-lipophilic balance values (from 12.4 to 16.7) with caraway EO caused a general inhibition of the repellent effect during the testing period (RI from +41% to −19%). Overall, the findings indicate that caraway EO could be used as a green peach aphid repellent, but more work is needed to formulate the EO into a ready-to-use product.